2009
DOI: 10.1016/j.cub.2009.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Somatotopy of Speech Perception

Abstract: Listening to speech recruits a network of fronto-temporo-parietal cortical areas. Classical models consider anterior (motor) sites to be involved in speech production whereas posterior sites are considered to be involved in comprehension. This functional segregation is challenged by action-perception theories suggesting that brain circuits for speech articulation and speech perception are functionally dependent. Although recent data show that speech listening elicits motor activities analogous to production, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
349
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(398 citation statements)
references
References 34 publications
44
349
4
1
Order By: Relevance
“…These motor and premotor activations are in accordance with previous studies on auditory, visual, and audiovisual speech perception showing a key role of motor regions in speech processing (e.g., d'Ausilio et al, 2009d'Ausilio et al, , 2011Sato et al, 2009Sato et al, , 2010Möttönen & Watkins, 2009;Meister et al, 2007;Skipper et al, 2005Skipper et al, , 2007Pekkola et al, 2006;Pulvermuller et al, 2006;Wilson & Iacoboni, 2006;Ojanen et al, 2005;Callan et al, 2003Callan et al, , 2004Watkins & Paus, 2004;Wilson et al, 2004;Calvert & Campbell, 2003;Watkins et al, 2003;Campbell et al, 2001;Calvert et al, 2000). It is worthwhile noting that, in this study, participants were only asked to attentively listen to and/or watch speech stimuli.…”
Section: Visuo-lingual and Visuo-facial Speech Stimuli Share A Commonsupporting
confidence: 91%
See 1 more Smart Citation
“…These motor and premotor activations are in accordance with previous studies on auditory, visual, and audiovisual speech perception showing a key role of motor regions in speech processing (e.g., d'Ausilio et al, 2009d'Ausilio et al, , 2011Sato et al, 2009Sato et al, , 2010Möttönen & Watkins, 2009;Meister et al, 2007;Skipper et al, 2005Skipper et al, , 2007Pekkola et al, 2006;Pulvermuller et al, 2006;Wilson & Iacoboni, 2006;Ojanen et al, 2005;Callan et al, 2003Callan et al, , 2004Watkins & Paus, 2004;Wilson et al, 2004;Calvert & Campbell, 2003;Watkins et al, 2003;Campbell et al, 2001;Calvert et al, 2000). It is worthwhile noting that, in this study, participants were only asked to attentively listen to and/or watch speech stimuli.…”
Section: Visuo-lingual and Visuo-facial Speech Stimuli Share A Commonsupporting
confidence: 91%
“…Brain areas involved in the planning and execution of speech actions (i.e., the posterior part of the left inferior frontal gyrus, the premotor and primary motor cortices) have indeed shown neural responses during auditory speech perception (e.g., Pulvermuller et al, 2006;Wilson & Iacoboni, 2006;Wilson, Saygin, Sereno, & Iacoboni, 2004). In addition, repetitive and double-pulse TMS studies also suggest that speech motor regions are causally recruited during auditory speech categorization, especially in case of complex situations (e.g., the perception of acoustically ambiguous syllables or when phonological segmentation or working memory processes are strongly required; d'Ausilio, Bufalari, Salmas, & Fadiga, 2011;d'Ausilio et al, 2009;Möttönen & Watkins, 2009;Sato, Tremblay, & Gracco, 2009;Meister, Wilson, Deblieck, Wu, & Iacoboni, 2007). Taken together, these results support the idea that our motor knowledge used to produce speech sounds helps to partly constraint phonetic decoding of the sensory inputs, as proposed in motor and sensorimotor theories of speech perception and language comprehension (Pickering & Garrod, 2013;Schwartz, Ménard, Basirat, & Sato, 2012;Skipper, Van Wassenhove, Nussman, & Small, 2007;Liberman & Mattingly, 1985).…”
Section: Motor Resonance Extends To Speech Actionmentioning
confidence: 99%
“…For example, in a speech perception task, strong activation in the motor cortex can be induced only when participants perceive the target speech [24,31] . Some studies using TMS of the motor cortex have demonstrated that stimulation of speech-related regions affects speech perception [32][33][34] . For example, using TMS to suppress the left premotor cortex, which is activated both during speech production and speech perception (Fig.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%
“…In this case, the operation of MMs is inferred when activity in a particular cortical area (as reflected in the BOLD signal) is similar during action recognition and action production, and when the cortical area is a likely homolog of an area in macaque cortex in which mirror neurons have been identified. Using this or a similar logic, it appears that the human MMs respond more to actions that the perceiver can perform than to actions the perceiver is familiar with through vision alone (Calvo-Merino et al, 2006); MMs are more sensitive to social actions than similar non-social actions (Kilner et al, 2006); MMs respond to both visually perceived actions and the linguistic description of actions (Tettamanti et al, 2005); MMs play a role in speech perception (D'Ausilio et al, 2009); activity in MMs is positively correlated with empathy (Gazzola et al, 2006) and negatively correlated with autistic behaviors (Dapretto et al, 2006). …”
Section: Introductionmentioning
confidence: 99%